2017
DOI: 10.33233/fb.v12i3.845
|View full text |Cite
|
Sign up to set email alerts
|

Exercí­cio fí­sico em pacientes portadores de diferentes ní­veis de doença pulmonar obstrutiva crônica

Abstract: Introdução: Uma importante consequência da dispneia é a limitação das atividades que piora com a progressão da doença, sendo a inatividade física o alvo na terapêutica da doença pulmonar obstrutiva crônica (DPOC). Objetivo: Verificar os efeitos do exercício físico em pacientes com diferentes níveis de DPOC submetidos a um programa de reabilitação pulmonar de longa duração. Materiais e métodos: Estudo descritivo e retrospectivo, com amostra de 40 prontuários de pacientes com DPOC que realizaram testes increment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The construction of this protocol made it possible to look together at a problem experienced every day, recovering its strengths and outlining conducts that can improve patient care in palliative care. 23 Still on pain relief, the study Living with pain: The Perspective of Children and Adolescents in Palliative Care reveals that patients under palliative care who use drugs and non-pharmacological alternatives, such as massage, hydrotherapy, acupuncture, and cryotherapy experience an improvement in their daily life. 24 From this perspective, it is found that symptom control, continuous commitment to the patient and family and physical, psychological, and spiritual support are essential care at the end of life.…”
Section: Resultsmentioning
confidence: 99%
“…The construction of this protocol made it possible to look together at a problem experienced every day, recovering its strengths and outlining conducts that can improve patient care in palliative care. 23 Still on pain relief, the study Living with pain: The Perspective of Children and Adolescents in Palliative Care reveals that patients under palliative care who use drugs and non-pharmacological alternatives, such as massage, hydrotherapy, acupuncture, and cryotherapy experience an improvement in their daily life. 24 From this perspective, it is found that symptom control, continuous commitment to the patient and family and physical, psychological, and spiritual support are essential care at the end of life.…”
Section: Resultsmentioning
confidence: 99%
“…(2021) reported that IMT may improve respiratory muscle strength, endurance, and exercise intolerance and reduce dyspnea. Also, aerobic exercises with IMT may have similar effects in improving cardiopulmonary and musculoskeletal function (El‐Hage Meyer de Barros Gulini et al., 2011). Similarly, the CPRG showed reduced dyspnea and fatigue after 6 weeks of rehabilitation.…”
Section: Discussionmentioning
confidence: 99%